Echinodermata Composition in Ngentup Beach and Banyu Meneng Beach, Malang Regency - Hasyim, Muhammad Asmuni; Nuha, Muhammad Ulin; Hanifa, Berry Fakhry (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2023)
Echinodermata is one of the main constituents of marine biodiversity that has an essential role in the marine ecosystem. The purpose of this study was to look at the composition of Echinodermata by looking at the diversity index, abundance, dominance, and similarity of the two Echinodermata locations found, as well as looking at supporting abiotic factors by correlating abiotic factors with the number of Echinodermata found at Ngentup Beach and Banyu Meneng Beach. The research was conducted in July-October with a purposive sampling method using line transects then the data was analyzed with the Microsoft Excel program and PAST v.4.03. This study obtained 9 species at Ngentup Beach and 11 species at Banyu Meneng Beach. The Echinodermata diversity index is 1.864 (Ngentup Beach) and 1.117 (Banyu Meneng Beach) respectively. The Echinodermata dominance index was 0.185 (Ngentup Beach) and 0.515 (Banyu Meneng Beach). Echinodermata abundance index was 0.042 in Tripneustes gratilla (Ngentup Beach) and 0.349 in Ophiocoma scolopendrina (Banyu Meneng Beach) with a similarity value of 0.387. Abiotic factor conditions at Ngentup Beach and Banyu Meneng Beach include pH 7.8, salinity 32.59%, temperature 27.2 oC, and DO 5.2 ppm, and at Banyu Meneng Beach pH 8.2, salinity 30.47%, 27.7 oC, and DO 5.57 ppm. The correlation test results showed a high correlation between Ophiocoma scolopendrina and the abiotic factor pH, namely 0.811 and Diadema setosum with the abiotic factors of salinity, temperature and DO, namely 0.869, 0.707 and 0.828.